A novel, variable angle guide grid for neuronal activity studies - Talbot, Thomas; Ide, David; Liu, Ning; Turchi, Janita (Frontiers in Integrative Neuroscience, 2012)
Introduction: Surgically implanted chambers with removable grids are routinely used for studying patterns of neuronal activity in primate brains; however, accessing target tissues is significantly constrained by standard grid designs. Typically, grids are configured with a series of guide holes drilled vertically, parallel to the walls of the chamber, thus targeted sites are limited to those in line vertically with one of the guide holes. Methods: By using the three-dimensional modeling software, a novel grid was designed to reach the targeted sites far beyond the standard reach of the chamber. The grid was fabricated using conventional machining techniques and three-dimensional printing. Results: A pilot study involving microinjection of the Magnetic resonance (MR) contrast agent gadolinium into the discrete regions of interest (ROIs) in the temporal cortex of an awake, behaving monkey demonstrated the effectiveness of this new design of the guide grid. Using multiple different angles of approach, we were readily able to access 10 injection sites, which were up to 5 mm outside the traditional, orthogonal reach of the chamber.